THE IMPACT OF NATIONAL HEALTH INSURANCE POLICY ON OUTPATIENT VISIT IN MALUKU AND PAPUA: LOGIT MODEL - Martaliza, Rira Wahdani; Pujiyanto, Pujiyanto (Journal of Indonesian Health Policy and Administration, 2020)
The National Health Insurance (JKN) is one manifestation of the National Social Security System program which aims to provide benefits for health care and protection. This study uses secondary data from the 2017 National Socio-Economic Survey (Susenas) which aims to prove that JKN ownership has an influence on outpatient visits. The research respondents were all people who were registered as JKN participants in the Maluku and Papua Islands regions as many as 77.307 people. This study uses the econometric approach with the Logit regression model. The results showed that JKN was positively associated with outpatient visits, with coefficients of PBI (0,713) and Non PBI (0,807). The results also showed that age had a positive effect on outpatient visits with a coeficent value (0,406), gender had a positive effect on outpatient visits with a coefficient (0,146), employment status negatively affected outpatient visits with a coefficient value (-0,198) likewise the health status has a positive effect on outpatient visits with a coefficient (3,914). JKN ownership has an important role for the community in fulfilling the utilization of health facilities when suffering from health complaints, one of which is the use of outpatient visits.